Best practices in public risk communication during enteric illness outbreak investigations: a scoping review - Mucević, Hana; McWhirter, Jennifer E.; Macleod, Jillian; Shereefdeen, Hisba; MacKay, Melissa; Cheng, Leslie; Phypers, Melissa; Grant, Lauren E. (Frontiers in Communication, 2025)
IntroductionPublic risk communication is intended to inform and protect the health of individuals during enteric illness outbreaks. However, there is limited practical research that assesses the effectiveness of communication during outbreaks. The aim of this study was to identify best practices in public risk communication during enteric illness outbreak investigations.MethodsA scoping review of five bibliographic databases and gray literature was conducted to identify studies that described public communication during foodborne, waterborne, or enteric zoonotic outbreaks. Eligibility criteria were applied to citations and then full text by two independent reviewers. Data from included studies was extracted and synthesized into categories. Evidence adequacy and agreement were assessed and used to assign an overall level of confidence for each best practice.ResultsIn total, 25 studies were included with most studies occurring in North America and Western Europe. Seven principles, nine practices, and eight platforms were identified. Of these, six principles, four practices, and two platforms received a high confidence rating in their overall effectiveness.DiscussionEffective risk communication during enteric illness outbreak investigations requires public health authorities to identify, characterize, tailor information to, and meaningfully engage with their target audiences, build relationships and collaborate with media outlets, and maintain and increase credibility to deliver trustworthy risk communication messages.